PEOPLE AND PLACES IN THE VITA OF HOSIOI NEKTARIOS AND THEOPHANES APSARAS - Agoritsas, Demetrios (Analecta Stagorum et Meteororum, 2022)
Hosioi Nektarios and Theophanes Apsaras (ca. 1470 - 1544/50) were important figures of post-Byzantine monasticism, during a time when Modern Hellenism strived to recover after the consolidation of ottoman rule, and reorganise socially, economically, spiritually, and ecclesiastically. The study of hagiographical texts and other contemporary sources related to the Apsaras brothers reveals two maniford personalities, descendants of a prominent family of Ioannina, who contributed greatly to the monastic renaissance of the sixteenth century. Besides the establisement and organisation of their monastic foundations, Nektarios and Theophanes also developed a widenetwork, which stretched from their homecity (Ioannina) and Constantinople to the distant Wallachia, and from their hermitage on the island of Ioannina to the monastic comunities of Meteora and Mount Athos. Their contacts included political and ecclesiastical authorities, as well as laymen, monks and other clerics. Moreover, it is worth noting the important role that the teachings and spiritual guidance of Saint Nephon (d. 1508), Patriarch of Constantinople, played in their later life. This network was characterized by variety, being shaped and influenced by the conditions and needs of their time. Furthermore, it reveals the two brothers’ dynamism and actions in a period of great danger, challenge and opportunity for Modern Hellenism. Apsaras brothers became a paradimg for other monastics as well, e.g., the founding fathers of the nearby Rousanou Monastery (Meteora), Joasaph and Maximos (ca. 1527-1529), who also came from Ioannina; while their spiritual legacy in Meteora and elsewhere was kept alive for a considertable period of time.